Psychosocial Profile and Use of Information and Communication Technologies by Students with High Academic Averages and a Minimal Presencial Educational Modality in a Mexican Context - Catalina María Rodríguez Pichardo; Alfonso Ávila Ortega; Mario Alberto González Medina; Yolanda Heredia Escorza (Universidad Autónoma de Baja California, 2008)
Ting and Robinson (1998) and Dimmitt (2003) present the need to study the topic of academic success including psychosocial aspects of the pupils. The objective of this research was to describe the psychosocial profile and the use of the Information and Communication Technologies (ICTs) of undergraduate students. The research design used for this purpose was non-experimental transectional descriptive. The instruments were a questionnaire for the Integral Profile of the Student and the Gordon Personal Profile Inventory. The sample consisted of 469 Mexican undergraduate pupils who receive traditional education. The results show that there is a significant difference statistically speaking according to the p value (0.000; 0.025; 0.004.000) obtained in the ANOVA for the cognitive and emotional areas, use of the ICTs and self-esteem of the surveyed students with high GPA.